Women Empowerment: Concept Paper - Masvikeni, Tecla; Kasu, Christine, Mary; Mugadza, Gladys (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
Women empowerment is the ability to say out views without belittling the other part. This involves the process of mutual dialogue, negotiation done to meet social needs. .Empowerment is the Process on a continuum to raise awareness, capacity building that leads to greater variety of participation, greater decision making power, control and transformative action.